FRI0637 Diagnostic performance of the new omeract criteria for cppd identification by us: correlation with synovial fluid analysis. (15th June 2017) - Adinolfi, A; Picerno, V; Scanu, A; Toscano, C; Scirè, CA; Carrara, G; Frediani, B; Iagnocco, A; Damjanov, N; Punzi, L; Filippou, G
Abstract : Background: Ultrasonography (US) has demonstrated to be an accurate tool for the diagnosis of calcium pyrophosphate deposition disease (CPPD) (1). Recently, the OMERACT "US in CPPD" subtask force, has created new definitions for CPPD identification by US, that demonstrated to be reliable at the knee joint, bridging a gap afflicting the old definitions (2). On the other hand, synovial fluid analysis (SFA) is considered to be an accurate and valid method for diagnosing CPPD. Objectives: The aim of this study wasto evaluate the association between US, using for the first time the new OMERACT US criteria for CPPD, and SFA findings for identifying patients affected by CPPD. Methods: We enrolled all the consecutive patients, aged more than 60 years old, referred to our outpatient clinic from September 2016 to December 2016, for knee pain and that presented knee effusion of any grade. Patients with suspected chronic inflammatory conditions were excluded. All the subjects underwent an US exam (EsaoteMyLab 70) of the clinically involved knee, performed by an expert sonographer that applied the new OMERACT criteria for the diagnosis of CPPD at the fibrocartilage (menisci) and hyaline cartilage of the affected knee (2). Subsequently, a US-guided arthrocentesis was performed, and the synovial fluid was collected and analyzed by a compensated polarized light microscopy (AxioLab A.1 [Zeiss]) by an expert observer in order to assess the presence of CPP crystals. Both observers were blinded to clinical and to each other findings. The Chi-squared test was used to correlate the US and SFA findings. Results: 49 patients (28 women) were enrolled in the study, with a mean age of 70, 29yo (SD±10, 93). 28 subjects were affected by CPPD at SFA and 26 patients were identified as affected by CPPD at US. In 4 patients, the SFA was positive and the US was negative, while in 2 patients the SFA was negative and the US positive. Using the chi-squared test, a very strong association was found between the exams, with a p-value <0, 0001. Conclusions: The new OMERACT US criteria for CPPD identification have already demonstrated to be reliable, considering the good to high kappa values yielded in previous multi-observer studies (2). This preliminary study, indicates that the new criteria seem to be also accurate for diagnostic purposes as they strongly correlate with the SFA for the presence of CPPD in knee joints. Further validation studies that will be able to assess the diagnostic accuracy of US are already in the research agenda of the OMERACT group "US in CPPD". References: Filippou G, Adinolfi A, Cimmino MA, Scirè CA, Carta S, Lorenzini S, et al. Diagnostic accuracy of ultrasound, conventional radiography and synovial fluid analysis in the diagnosis of calcium pyrophosphate dihydrate crystal deposition disease. ClinExpRheumatol 2016. Filippou G, Scirè CA, Damjanov N et al. Definition and reliability assessment of elementary ultrasonographic findings in Calcium Pyrophosphate Deposition Disease. Results of an international multi-observer study by the OMERACT "US in CPPD" sub-task force. J Rheumatol, in press. Disclosure of Interest: None declared